2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00919
|View full text |Cite
|
Sign up to set email alerts
|

Deep Floor Plan Recognition Using a Multi-Task Network With Room-Boundary-Guided Attention

Abstract: This paper presents a new approach to recognize elements in floor plan layouts. Besides walls and rooms, we aim to recognize diverse floor plan elements, such as doors, windows and different types of rooms, in the floor layouts. To this end, we model a hierarchy of floor plan elements and design a deep multi-task neural network with two tasks: one to learn to predict room-boundary elements, and the other to predict rooms with types. More importantly, we formulate the room-boundary-guided attention mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 21 publications
1
108
0
Order By: Relevance
“…The proposed framework outputs the result in a vector format, which facilitates its use in additional research or real-world applications. For example, Zeng et al [10] demonstrated the 3D models of the results from their method, and the output of the proposed framework is already vector-type data, making it even easier for 3D modeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed framework outputs the result in a vector format, which facilitates its use in additional research or real-world applications. For example, Zeng et al [10] demonstrated the 3D models of the results from their method, and the output of the proposed framework is already vector-type data, making it even easier for 3D modeling.…”
Section: Discussionmentioning
confidence: 99%
“…They also used OCR to be able to recognize the size of the rooms and to place furniture models scaled to the scene. Zeng et al [10] proposed a method that detects and classifies walls, doors, windows, and rooms by training a VGG encoder-decoder. Unlike [8], their method is applicable to non-rectangular shape elements and is able to obtain the shape features of indoor elements.…”
Section: Rule-based Heuristic Methods and Machine Learning Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this algorithm lacks robustness for unseen elements. A deep multi-task neural network was proposed to identify room types and walls (Zeng et al 2019). Compared with the Raster-to-Vector algorithm (Liu et al 2017), this algorithm has higher precision.…”
Section: Ai-based Bim Model Generationmentioning
confidence: 99%